Pemanfaatan Portal Rumah Belajar untuk Media Pembelajaran Daring di Era Pandemi Covid-19 - Marlina, Betty (Yayasan Sembilan Pemuda Indonesia, 2021)
The purpose of this study is to describe how the Ministry of Education and Culture's Learning Center Portal was used as an online learning medium during the Covid-19 pandemic. The descriptive qualitative method was used in this research. Semi-structured interviews with teachers at different levels of education in South Sumatra Province were used to collect data. The findings of this study show that learning materials, virtual labs, virtual classes, and question banks are all useful features of the Learning House Portal as a learning medium. These online learning activities are carried out using the Ministry of Education and Culture learning house portal media through the WhatsApp group or via google classroom. The learning house portal is very useful as an online learning medium during the Covid-19 pandemic by taking advantage of the many features available.